Role of Cloud Computing in Data Mining (International Journal of Engineering and Computer Science, 2016)
Data Mining is a procedure of extracting potentially helpful information from raw data, so as to get better the excellence of the information service. Cloud computing can give infrastructure to huge and multifaceted data of data mining, in addition to innovative demanding issues for data mining of cloud computing research are emerged. This paper introduces the essential thought of cloud computing and data mining and their security.